STATUS SOSIAL EKONOMI DAN FERTILITAS: A Latent Variable Approach - Suandi - (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2010)
The main problems faced by developing countries including Indonesia are not onlyeconomic problems that tend to harm, but still met the high fertility rate. The purpose ofwriting to find out the relationship between socioeconomic status to the level of fertilitythrough the